Effect of Activated Carbon on Cellulose Nanofiber Aerogels for Enhanced Solar Steam Generation - Barus, Diana Alemin; Kevin Nainggolan (Talenta Publisher, 2024)
The development of efficient and environmentally friendly clean water production systems is becoming increasingly important. This study focuses on an innovative evaporator for a Solar Steam Generator (SSG) system designed to produce clean water using accessible materials. The SSG evaporator is constructed from cellulose bonded with Polyvinyl Alcohol (PVA) and incorporates a freeze-drying method to enhance porosity, which improves water delivery within the SSG system. To further boost the efficiency of the evaporator, activated carbon (AC) is added due to its effective absorption of visible to infrared radiation. Evaporation rate testing demonstrates that the addition of 3 wt% AC yields an evaporation rate of 1.39 kg/mÂ²/h and an efficiency of 58.56%. Fourier-transform infrared (FTIR) spectroscopy was employed to analyze changes in the sample after AC addition and to examine infrared absorption characteristics.